Human papillomavirus (HPV) 16 antibodies at diagnosis of HPV-related oropharyngeal cancer and antibody trajectories after treatment. (April 2017) - Zhang, Yuehan; Waterboer, Tim; Haddad, Robert I.; Miles, Brett A.; Wentz, Alicia; Gross, Neil D.; Fakhry, Carole; Quon, Harry; Lorch, Jochen H.; Gourin, Christine G.; Clayburgh, Daniel; Misiukiewicz, Krzysztof J.; et al.
Highlights: At cancer diagnosis, most HPV-OPC cases were seropositive to HPV16 E6. HPV16 E6 antibody levels drop after treatment, but levels remain high in most HPV-OPC cases. HPV16 E6 antibody levels at diagnosis did not predict cancer recurrence. Abstract: Objectives: Despite the fact that HPV-driven oropharyngeal cancer (HPV-OPC) has relatively low recurrence rates, intensive post-therapy monitoring remains the standard of care. Post-treatment biomarkers are needed to risk stratify HPV-OPC patients for more individualized surveillance intensity and which remain at higher recurrence risk. Materials and Methods: 115 HPV-OPC patients (ascertained by p16 immunohistochemistry and/or in-situ hybridization) from a multicenter prospective case study (HOTSPOT) had blood collected at diagnosis, and 64 of these also had blood collected at post-treatment follow-up visits for up to two years. Samples were centrally tested for antibodies to the L1, E1, E2, E4, E6, and E7 proteins of HPV16. Results: At diagnosis, most HPV-OPC cases were seropositive to HPV16 E6 (85%). In post therapeutic samples, HPV16 antibody level decreased slowly over time, but only 3 (of 51 cases seropositive at enrollment) dropped low enough to be classified as seronegative. At 3 years after diagnosis, cumulative risk of recurrence was 10.2% and 0% in HPV16 E6 seropositive and E6 seronegative HPV-OPC cases, respectively (p = 0.18). Risk of recurrence was increased, although not statistically significant, in those with higher HPV16 E6 antibody levels at diagnosis (per log antibody level, hazard ratio [HR] = 1.81, 95%CI = 0.47–6.92). Conclusion: This study confirms the high seroprevalence of HPV oncogenic antibodies at diagnosis of HPV-OPC. HPV16 E6 antibody levels decrease after treatment, but most cases remain seropositive for up to two years. HPV16 E6 antibody levels at diagnosis did not appear to be a strong predictor of recurrence.